The Impact of Parental Involvement in Preschool on Children’s Academic Performance - Nair, Subadrah Madhawa; Wider, Walton; Bo, Ding; Singh, Gurdip Kaur Saminder; Siddique, Muhammad (Journal of Ecohumanism, 2024)
This study aims to examine whether there is a correlation between parental involvement in preschool and children’s academic performance. The study also investigated whether parental involvement (home-based, school-based and home-school conferencing) have an impact on pre-school children’s academic performance. In addition, this study also investigated the effects of parents’ gender, level of education and income on young learners’ academic success at school. This study employed a descriptive research design and used questionnaire to collect the data. The sample consists of 400 parents from five preschools in Henan district, China. Stratified random sampling was used in choosing the sample. The data of the study were analyzed using independent correlation, regression, independent samples t-test and one-way ANOVA. The results revealed that there is a significant positive correlation between parental involvement (home-based involvement, school-based involvement and home-school conferencing) and preschoolers' academic performance. The findings also showed that female parents were more engaged than male parents at preschool. Results of the ANOVA test revealed that parents with higher level of education and higher income were significantly more involved in preschool compared to their counterparts with lower level of education and lower income. These findings are crucial for policy makers to take the right measures in enhancing parental involvement in preschool.